Ladybird read with me: practice and play (key words to reading) 6 - Murray, W.; Corby, Jill Dwyer, Derek Trotter, Stuart (Ladybird Loughborough, Leics., 1993)
A practice and play book which is one of the Read with Me series, which is intended to cover the three main methods of teaching reading. Its publication coincides with the launch of the new phonic scheme Say the Sounds and has a simplified message to parents.